A Fluorescent Gram Stain for Flow Cytometry and Epifluorescence Microscopy - Mason, David J. (American Society for Microbiology, 1998)
The fluorescent nucleic acid binding dyes hexidium iodide (HI) and SYTO 13 were used in combination as a Gram stain for unfixed organisms in suspension. HI penetrated gram-positive but not gram-negative organisms, whereas SYTO 13 penetrated both. When the dyes were used together, gram-negative organisms were rendered green fluorescent by SYTO 13; conversely, gram-positive organisms were rendered red-orange fluorescent by HI, which simultaneously quenched SYTO 13 green fluorescence. The technique correctly predicted the Gram status of 45 strains of clinically relevant organisms, including several known to be gram variable. In addition, representative strains of gram-positive anaerobic organisms, normally decolorized during the traditional Gram stain procedure, were classified correctly by this method.